Breast Skin Temperature Evaluation in Lactating and Non-lactating Women by Thermography: An Exploratory Study - Gouveia, Ana (2022)
During pregnancy and lactation, woman breasts feel changes like blood flow increasement, associated with a higher breast temperature. We performed an exploratory study of the breast skin temperature of lactating and non-lactating women based on thermography, with a qualitative analysis of the temperature patterns and a quantitative evaluation of the differences. Frontal breast thermograms of four non-lactating young women and four women with well-established lactation were acquired and analyzed. Qualitative analysis of the images obtained show some evidence of the existence of a characteristic skin temperature pattern for lactating women. Quantitative differences between thermograms were also noticed, especially when considering dispersion metrics: lactating women present higher breast skin temperature gradients and amplitudes. Results obtained, especially based on central tendency metrics, should be interpreted with caution because some of the acquisition conditions for non-lactating women may lead to some bias on the results. Further investigation will be performed to quantify breast skin temperature gradient and be able to classify images based in the breast skin temperature pattern.